2004
DOI: 10.1016/j.physc.2003.09.103
|View full text |Cite
|
Sign up to set email alerts
|

Fluxon dynamics by microwave surface resistance measurements in MgB2

Abstract: Field-induced variations of the microwave surface resistance, R s (H), have been investigated in high-density ceramic MgB 2 . At low temperatures, several peculiarities of the R s (H) curves cannot be justified in the framework of models reported in the literature. We suggest that they are ascribable to the unconventional vortex structure in MgB 2 , related to the presence of two gaps. On the contrary, the results near T c can be accounted for by the Coffey and Clem model, with fluxons moving in the flux-flow … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…As already mentioned, results very similar to those reported in this paper have been obtained in all the MgB 2 bulk samples we have investigated [11][12][13], except in a strongly irradiated MgB 2 bulk sample, in which the two gaps merged into a single value [11]. Moreover, the anomalous plateau in the decreasing-field branch of the R s (H 0 ) curve has not been observed in samples of MgB 2 consisting of fine powder [13].…”
Section: Analysis Of the Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…As already mentioned, results very similar to those reported in this paper have been obtained in all the MgB 2 bulk samples we have investigated [11][12][13], except in a strongly irradiated MgB 2 bulk sample, in which the two gaps merged into a single value [11]. Moreover, the anomalous plateau in the decreasing-field branch of the R s (H 0 ) curve has not been observed in samples of MgB 2 consisting of fine powder [13].…”
Section: Analysis Of the Resultssupporting
confidence: 89%
“…Studies reported in the literature on the field-induced variations of R s in MgB 2 have highlighted several anomalies, especially at applied magnetic fields much lower than the upper critical field, among which are unusually enhanced field-induced mw losses [8][9][10][11] and a magnetic hysteresis of unconventional shape [11][12][13]. It has been suggested that these anomalies are strictly related to the peculiarities of the fluxon lattice in MgB 2 .…”
Section: Introductionmentioning
confidence: 99%